2013
DOI: 10.1080/02786826.2013.787157
|View full text |Cite
|
Sign up to set email alerts
|

Deposition Uniformity of Coal Dust on Filters and Its Effect on the Accuracy of FTIR Analyses for Silica

Abstract: Miners are exposed to silica-bearing dust which can lead to silicosis, a potentially fatal lung disease. Currently, airborne silica is measured by collecting filter samples and sending them to a laboratory for analysis. Since this may take weeks, a field method is needed to inform decisions aimed at reducing exposures. This study investigates a field-portable Fourier transform infrared (FTIR) method for end-of-shift (EOS) measurement of silica on filter samples. Since the method entails localized analyses, spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Closed face sampling at a flow rate of 4 L/min was conducted for the TSP sampling. Such sampling conditions may have resulted in an uneven deposit on the filter (Miller et al, 2013), invalidating the assumption made that the ~1.5 cm 2 punch analyzed was representative of the entire filter. As a result, reported TSP concentrations for OC-EC may be overestimated.…”
Section: Direct-reading Instrumentsmentioning
confidence: 95%
“…Closed face sampling at a flow rate of 4 L/min was conducted for the TSP sampling. Such sampling conditions may have resulted in an uneven deposit on the filter (Miller et al, 2013), invalidating the assumption made that the ~1.5 cm 2 punch analyzed was representative of the entire filter. As a result, reported TSP concentrations for OC-EC may be overestimated.…”
Section: Direct-reading Instrumentsmentioning
confidence: 95%
“…7 The chamber, with a hexagonal cross section is 2.44 m high with an inside diameter of 1.19 m. The dust was introduced at the top of the chamber and thoroughly mixed in this region by the energy of an air jet entering at the side of the chamber. From this mixing area, the dust flows downward through a 10-cm thick honeycomb structure where turbulence in the air is reduced, providing a low velocity downward flow through the test section portion of the chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Deposition profiles of respirable coal dust, with sample-to-sample variation, changed slightly as filter loading increased when samples were collected with 10-mm nylon cyclones. 7 Different deposition profiles of coal dust were also found on filters from different sampling cassettes (2-piece, 3-piece, MSA cassette) collected with 10-mm nylon cyclone. 7 The deposition profiles generated by various low-flow and high-flow rate samplers were also investigated with respirable metal mine dust.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…14 Specifically, preliminary investigations using a limited set of laboratory-prepared samples concluded that RCS determination using DoF IR analysis for lab-generated coal dusts is not substantially impacted by current sampling equipment and methodologies. 14,15 …”
Section: Introductionmentioning
confidence: 99%